Development Of Computer-Assisted Chemistry Learning Media With The Macromedia Flash Program To Measure Problem-Solving Abilities - Afni, Khairul; Silaban, Ramlan (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2023)
Efforts to improve the quality of education are influenced by the factors involved during the learning process; such as teachers, curriculum, infrastructure, and the environment. This is in line with Law no. 20 of 2003 which states that "Learning is a process of student interaction and learning resources in a learning environment". Over time, the foundations of the world of education began to be neglected, so that UNESCO (United Nations Education Scientific and Cultural Organization) initiated four pillars of education to improve the quality of education, namely: Learning to know, learning to do, learning to be, and learning to live together. To realize the four pillars of education in the current era of information globalization, teachers as learning agents are required to master and apply Information and Communication Technology in learning. This study aims to measure students' problem solving abilities using macromedia flash chemistry learning media. This type of research is R&D. The subjects in this study were 35 students of class X SMA Negeri 4 Binjai. The data taken is in the form of the results of the feasibility of macromedia flash-based chemistry learning media in measuring students' problem-solving abilities and the responses given. From the data generated, 95.71% of students gave positive responses and out of 35 students there were 2 students who had very low scores, so it can be concluded that macromedia flash-based chemistry learning media can be used